Virgin coconut oil extract mitigates testicular‐induced toxicity of alcohol use in antiretroviral therapy. (14th April 2018) - Ogedengbe, O. O.; Naidu, E. C. S.; Akang, E. N.; Offor, U.; Onanuga, I. O.; Peter, A. I.; Jegede, A. I.; Azu, O. O.
Summary: The consumption of alcohol by people living with HIV/AIDS is associated with a graver prognosis. Long‐term use of antiretrovirals may have certain health challenges that may be aggravated by concomitant alcohol use. This study investigated virgin coconut oil (VCO) as an adjuvant to the deleterious effects of highly active antiretroviral therapy (HAART) and alcohol on the cyto‐architecture and functioning of the testis. Forty adult male Sprague‐Dawley rats, weighing 165~176 g, were divided into eight groups and treated according to protocol. Testicular histology, stereological parameters, seminal fluid, testosterone, luteinizing hormone, follicle‐stimulating hormone, the antioxidants marker malondialdehyde (MDA), and antioxidant glutathione (GSH) were examined. The use of ethanol alone and ethanol + HAART showed extensive degeneration in the seminiferous epithelium, decreased semen quality, disorganized basement membrane and widened, hypocellular interstitium. GSH was significantly decreased in the ethanol alone treated group with no significant effect on testosterone, LH, and MDA levels. Adjuvant treatment with VCO at low dose (2.5 mL/kg/bw) improved sperm motility with a partial restoration of the histopathological alterations. High doses of VCO (5.0 mL/kg/bw) showed greater improvement with respect to sperm counts, increased FSH hormonal and GSH antioxidant levels, and a well‐preserved testicular cyto‐architecture.